Catch-up-ESUS - follow-up in embolic stroke of undetermined source (ESUS) in a prospective, open-label, observational study: study protocol and initial baseline data. Issue 12 (9th December 2019) - Feil, Katharina; Heinrich, Johanna; Küpper, Clemens; Müller, Katharina; Laub, Christoph; von Falkenhausen, Aenne S; Becker, Regina; Wollenweber, Frank A; Kääb, Stefan; Sinner, Moritz F; Kellert, Lars
Abstract : Introduction: So far there is no uniform, commonly accepted diagnostic and therapeutic algorithm for patients with embolic stroke of undetermined source (ESUS). Recent clinical trials on secondary stroke prevention in ESUS did not support the use of oral anticoagulation. As ESUS comprises heterogeneous subgroups including a wide age-range, concomitant patent foramen ovale (PFO), and variable probability for atrial fibrillation (AF), an individualised approach is urgently needed. This prospective registry study aims to provide initial data towards an individual, structured diagnostic and therapeutic approach in ESUS patients. Methods and analysis: The open-label, investigator-initiated, prospective, single-centre, observational registry study (Catch-up-ESUS) started in 01/2018. Consecutive ESUS patients ≥18 years who give informed consent are included and will be followed up for 3 years. Stratified by age <60 or ≥60 years, the patients are processed following a standardised diagnostic and treatment algorithm with an interdisciplinary design involving neurologists and cardiologists. Depending on the strata, patients receive a transesophageal echocardiogram; all patients receive an implantable cardiac monitor. Patients <60 years with PFO and without evidence of concomitant AF are planned for PFO closure within 6 months after stroke. The current diagnostic and therapeutic workup of ESUS patients requires improvement by both standardisation and a more individualised approach. Catch-up-ESUS will provide important data with respect to AF detection and PFO closure and will estimate stratified stroke recurrence rates after ESUS. Ethics and dissemination: The study has been approved by the responsible ethics committee at the Ludwig Maximilian University, Munich, Germany (project number 17–685). Catch-Up-ESUS is conducted in accordance with the Declaration of Helsinki. All patients will have to give written informed consent or, if unable to give consent themselves, their legal guardian will have to provide written informed consent for their participation. The first observation period of the registry study is 1 year, followed by the first publication of the results including follow-up of the patients. Further publications will be considered according the predefined individual follow-up dates of the stroke patients up to 36 months. Trial registration number: Clinicaltrialsregister.gov registry (NCT03820375 ).